Leptin Deficiency Causes Insulin Resistance Induced by Uncontrolled Diabetes - German, Jonathan P. (American Diabetes Association, 2010)
OBJECTIVE: Depletion of body fat stores during uncontrolled, insulin-deficient diabetes (uDM) results in markedly reduced plasma leptin levels. This study investigated the role of leptin deficiency in the genesis of severe insulin resistance and related metabolic and neuroendocrine derangements induced by uDM. RESEARCH DESIGN AND METHODS: Adult male Wistar rats remained nondiabetic or were injected with the β-cell toxin, streptozotocin (STZ) to induce uDM and subsequently underwent subcutaneous implantation of an osmotic minipump containing either vehicle or leptin at a dose (150 μg/kg/day) designed to replace leptin at nondiabetic plasma levels. To control for leptin effects on food intake, another group of STZ-injected animals were pair fed to the intake of those receiving leptin. Food intake, body weight, and blood glucose levels were measured daily, with body composition and indirect calorimetry performed on day 11, and an insulin tolerance test to measure insulin sensitivity performed on day 16. Plasma hormone and substrate levels, hepatic gluconeogenic gene expression, and measures of tissue insulin signal transduction were also measured. RESULTS: Physiologic leptin replacement prevented insulin resistance in uDM via a mechanism unrelated to changes in food intake or body weight. This effect was associated with reduced total body fat and hepatic triglyceride content, preservation of lean mass, and improved insulin signal transduction via the insulin receptor substrate–phosphatidylinositol-3-hydroxy kinase pathway in the liver, but not in skeletal muscle or adipose tissue. Although physiologic leptin replacement lowered blood glucose levels only slightly, it fully normalized elevated plasma glucagon and corticosterone levels and reversed the increased hepatic expression of gluconeogenic enzymes characteristic of rats with uDM. CONCLUSIONS: We conclude that leptin deficiency plays a key role in the pathogenesis of severe insulin resistance and related endocrine disorders in uDM. Treatment of diabetes in humans may benefit from correction of leptin deficiency as well as insulin deficiency.